Interactions Between Potentially Toxic Nanoparticles (Cu, CuO, ZnO, and TiO2) and the Cyanobacterium Arthrospira platensis: Biological Adaptations to Xenobiotics - Ludmila Rudi; Liliana Cepoi; Tatiana Chiriac; Svetlana Djur (Nanomaterials)
(1) Background: The widespread use of nanoparticles (NPs) implies their inevitable contact with living organisms, including aquatic microorganisms, making it essential to understand the effects and consequences of this interaction. Understanding the adaptive responses and biochemical changes in microalgae and cyanobacteria under NP-induced stress is essential for developing biotechnological strategies that optimize biomolecule production while minimizing potential toxicity. This study aimed to evaluate the interactions between various potentially toxic nanoparticles and the cyanobacterial strain Arthrospira platensis, focusing on the biological adaptations and biochemical mechanisms that enable the organism to withstand xenobiotic exposure. (2) Methods: The cyanobacterium Arthrospira platensis CNMN-CB-02 was cultivated under optimal laboratory conditions in the presence of CuNPs, CuONPs, ZnONPs, and TiO2NPs. Biochemical analyses were performed on the collected biomass. (3) Results: Various interactions between nanoparticles (NPs) and the cyanobacterial culture were identified, ranging from hormetic effects at low concentrations to evident toxic effects at high concentrations. NP toxicity was observed through the reduction in photosynthetic pigments and the disappearance of phycobiliproteins. Notably, NP toxicity was not always accompanied by increased malondialdehyde (MDA) levels. (4) Conclusions: Arthrospira platensis exhibits unique adaptive mechanisms under NP-induced stress, offering the potential for controlled NP applications in biotechnology. Future research should further explore the relationship between nanoparticle types and cyanobacterial responses to optimize biomolecule production.